Be ready when the luck happens ebook A memoir. - Garten, Ina (2024)
#1 NEW YORK TIMES BESTSELLER • In her long-awaited memoir, Ina Garten—aka the Barefoot Contessa, author of thirteen bestselling cookbooks, beloved Food Network personality, Instagram sensation, and cultural icon—shares her personal story with readers hungry for a seat at her table. A BEST BOOK OF THE YEAR: The New York Times Book Review , Time, The New Yorker, Vanity Fair, Town & Country Here, for the first time, Ina Garten presents an intimate, entertaining, and inspiring account of her remarkable journey. Ina’s gift is to make everything look easy, yet all her accomplishments have been the result of hard work, audacious choices, and exquisite attention to detail. In her unmistakable voice (no one tells a story like Ina), she brings her past and her process to life in a high-spirited and no-holds-barred memoir that chronicles decades of personal challenges, adventures (and misadventures) and unexpected career twists, all delivered with her signature combination of playfulness and purpose.   From a difficult childhood to meeting the love of her life, Jeffrey, and marrying him while still in college, from a boring bureaucratic job in Washington, D.C., to answering an ad for a specialty food store in the Hamptons, from the owner of one Barefoot Contessa shop to author of bestselling cookbooks and celebrated television host, Ina has blazed her own trail and, in the meantime, taught millions of people how to cook and entertain. Now, she invites them to come closer to experience her story in vivid detail and to share the important life lessons she learned along the way: do what you love because if you love it you’ll be really good at it, swing for the fences, and always Be Ready When the Luck Happens .